2017
DOI: 10.1007/s11250-017-1347-z
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Salmonellae isolated in Japanese quails reared in Abeokuta, Nigeria

Abstract: Salmonellosis is a major bacterial disease causing huge economic losses in the poultry industry worldwide. This study was carried out to determine the period prevalence and antimicrobial susceptibility of Salmonella enterica in Japanese quails in Abeokuta, Nigeria. Four hundred cloacal swabs of quail birds were collected from 4 locations within Abeokuta. Salmonella was isolated from the samples using conventional methods for selective isolation of Salmonella and biochemical identification. Isolates were confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
3
7
2
Order By: Relevance
“…This is similar to other reports where Salmonella isolates from chickens and Japanese quails showed a high level of resistance to ampicillin (80.0% to 100%) and tetracycline (35% to 100%) (Ojo et al, 2012;Omoshaba et al, 2017). The rates of resistance to gentamicin (6.7% in Salmonella and 9.1% in Yersinia) observed in this study were lower than that of 21.4% reported in Salmonella in Japanese quails (Omoshaba et al, 2017). Similarly, Salmonella and Yersinia isolates from this study showed a lower level of resistance to streptomycin (6.7% and 27.3, respectively) than the 57.2% resistance reported in Salmonella in Japanese quails (Omoshaba et al, 2017).…”
Section: ■ Conclusionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is similar to other reports where Salmonella isolates from chickens and Japanese quails showed a high level of resistance to ampicillin (80.0% to 100%) and tetracycline (35% to 100%) (Ojo et al, 2012;Omoshaba et al, 2017). The rates of resistance to gentamicin (6.7% in Salmonella and 9.1% in Yersinia) observed in this study were lower than that of 21.4% reported in Salmonella in Japanese quails (Omoshaba et al, 2017). Similarly, Salmonella and Yersinia isolates from this study showed a lower level of resistance to streptomycin (6.7% and 27.3, respectively) than the 57.2% resistance reported in Salmonella in Japanese quails (Omoshaba et al, 2017).…”
Section: ■ Conclusionsupporting
confidence: 92%
“…In our study salmonellae and yersiniae also showed a very high degree of resistance to ampicillin and tetracycline, which are the most commonly used antimicrobial agents in veterinary and human medical practices (Ojo et al, 2017). This is similar to other reports where Salmonella isolates from chickens and Japanese quails showed a high level of resistance to ampicillin (80.0% to 100%) and tetracycline (35% to 100%) (Ojo et al, 2012;Omoshaba et al, 2017). The rates of resistance to gentamicin (6.7% in Salmonella and 9.1% in Yersinia) observed in this study were lower than that of 21.4% reported in Salmonella in Japanese quails (Omoshaba et al, 2017).…”
Section: ■ Conclusionsupporting
confidence: 90%
See 3 more Smart Citations